Implementasi Sertifikat Elektronik Sebagai Jaminan Kepastian Hukum Kepemilikan Hak Atas Tanah di Indonesia - Nur Hidayani Alimuddin (SASI, 2021)
The occurrence of falsification of land certificates, multiple land certificates or overlapping land certificates and the rampant land mafia are the causes of various land disputes which will ultimately harm the citizen. This means that land rights certificates no longer provide legal certainty for the citizen. So basically the government does need a new legal breakthrough by the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 1 of 2021 concerning Electronic Certificates. The type of research used in this research is normative legal research (doctrinal legal research). The approach method in this study uses a statutory approach, an approach using legislation and regulations. The results of this study are the mechanism of the land registration system based on an electronic system will produce an output in the form of an electronic document in the form of an electronic certificate (e-certificate). The e-certificate will provide benefits to the citizen in the form of easy access to digital data and will be free from falsification of land certificates which are the basis for guaranteeing legal certainty for ownership of land rights.